Physicians' conceptualization of "Closure" as A benefit of Physician-Parent Follow-Up Meetings after A Child's Death in the Pediatric Intensive Care Unit. Issue 2 (June 2013) - Eggly, Susan; Meert, Kathleen L.; Berger, John; Zimmerman, Jerry; Anand, K.J.S.; Newth, Christopher J.L.; Harrison, Rick; Carcillo, Joseph; Dean, J. Michael; Willson, Douglas F.; Nicholson, Carol
We examined physicians' conceptualization of closure as a benefit of follow-up meetings with bereaved parents. The frequency of use and the meaning of the word "closure" were analyzed in transcripts of interviews with 67 critical care physicians affiliated with the Collaborative Pediatric Critical Care Research Network. In all, 38 physicians (57 percent) used the word "closure" at least once (median: 2; range: 1 to 7), for a total of 86 times. Physicians indicated that closure is a process or trajectory rather than an achievable goal. They also indicated that parents and physicians can move toward closure by gaining a better understanding of the causes and circumstances of the death and by reconnecting with, or resolving relationships between, parents and health professionals. Physicians suggested that a primary reason to conduct follow-up meetings is that such meetings offer parents and physicians an opportunity to move toward closure. Future research should attempt to determine whether follow-up meetings reduce the negative effects of bereavement for parents and physicians.